Experiences of the Creative Doctorate: Minstrels and White Lines - Wisker, Gina; Robinson, Gillian (Critical Studies in Teaching and Learning, 2023)
Relationships between the expectations of the PhD, creativity and identity are a rich terrain for research, explored here. Doctoral student identity and the expectations of the PhD have been the focus of much previous work, while work on candidates pursuing research in literature and art has focused on tensions in their work, and the conceptual threshold crossings they make during the PhD journey. The research discussed here explores tensions and rich relationships between creativity, identity and success for candidates self-defined as ’creative’ engaged in doctorates ranging between art or literary practice, and creative work in professional contexts.